Transient pockets as mediators of gas molecules routes inside proteins: The case study of dioxygen pathway in homogentisate 1, 2-dioxygenase and its implication in Alkaptonuria development. (October 2020) - Bernini, Andrea; Galderisi, Silvia; Spiga, Ottavia; Amarabom, Chukwudi Onyekachi; Santucci, Annalisa
Graphical abstract: Highlights: By use of Implicit Ligand Sampling, approach routes for dioxygen to the active site of homogentisate 1, 2-dioxygenase were delineated. Along the dioxygen route the E401Q variant, responsible for the rare disease Alkaptonuria, disrupts the gas diffusion path. The diffusion of dioxygen is mediated by a transient pocket, suggesting transient geometry has to be taken into account for small molecules diffusion trough protein moiety. Abstract: Alkaptonuria (AKU) is an ultra-rare disease caused by mutations in homogentisate 1, 2-dioxygenase (HGD) enzyme, characterized by the loss of enzymatic activity and the accumulation of its substrate, homogentisic acid (HGA) in different tissues, leading to ochronosis and organ degeneration. Although the pathological effects of HGD mutations are largely studied, less is known about the structure of the enzyme, in particular the pathways for dioxygen diffusion to the active site, required for the enzymatic reaction, are still uninvestigated. In the present project, the combination of two in silico techniques, Molecular Dynamics (MD) simulation and Implicit Ligand Sampling (ILS), was used to delineate gas diffusion routes in HGD enzyme. A route from the central opening of the hexameric structure of the enzyme to the back of the active site trough the protein moiety was identified as the path for dioxygen diffusion, also overlapping with a transient pocket, which then assumes an important role in dioxygen diffusion. Along the route the sequence location of the missense variant E401Q, responsible for AKU development, was also found, suggesting such mutation to be conducive of enzymatic activity loss by altering the flow dynamics of dioxygen. Our in silico approach allowed also to delineate the route of HGA substrate to the active site, until now only supposed.